The Implementation of PSAK 109 on Infaq Shadaqah Funds in Zakat Institutions (Study in DMC Dompet Dhuafa) - Yudi Yudiana (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2020)
This study aims to determine the application of infaq and alms accounting based on PSAK 109 which focuses on the presentation of financial reports on DMC organs as a network of Dompet Dhuafa amil zakat institutions in the field of disasters which mostly manages infak/sedekah funds in its operations. This research is a qualitative study of critical discourse analysis, which is a method by collecting, preparing, and analyzing data in the form of organizational financial reports so that later it can provide a clear picture of the application of infak and sedekah accounting based on PSAK 109 in the DMC organ. The data processing method uses interviews with related documents and is accompanied by one of the validity of the data, namely triangulation. The results showed errors in understanding and applying the recording method will affect the decision making strategy and goal orientation of the non-profit organization. The role of the leader is the key to success in disseminating it, as well as setting it in the form of an Operating Procedure System.